Lenalidomide maintenance in patients with relapsed diffuse large B-cell lymphoma who are not eligible for autologous stem cell transplantation: an open label, single-arm, multicentre phase 2 trial. Issue 3 (March 2017) - Ferreri, Andrés J M; Sassone, Marianna; Zaja, Francesco; Re, Alessandro; Spina, Michele; Rocco, Alice Di; Fabbri, Alberto; Stelitano, Caterina; Frezzato, Maurizio; Rusconi, Chiara; Zambello, Renato; Couto, Suzana; et al.
Summary: Background: Patients with relapsed diffuse large B-cell lymphoma (DLBCL) not eligible for autologous stem cell transplantation (ASCT) or having relapse after ASCT have a low likelihood of cure. Single-drug maintenance after salvage therapy might be an attractive strategy to prolong survival in these patients. Lenalidomide is a suitable candidate for long-lasting maintenance as it is an oral drug, active against DLBCL that can be taken for years with an acceptable toxicity profile. We designed a study to investigate safety and efficacy of lenalidomide maintenance in patients with chemosensitive relapse of DLBCL not eligible for ASCT or having relapse after ASCT. Methods: In this open-label, single group, multicentre phase 2 trial, we recruited HIV-negative adults with de novo or transformed DLBCL and relapsed disease responsive to conventional rituximab-containing salvage therapy from 12 oncology-haematology centres in Italy. All patients were given oral lenalidomide 25 mg per day for 21 of 28 days until lymphoma progression or unacceptable toxicity (severely compromises organ function, quality of life, or both). Primary endpoint was 1-year progression-free survival. The estimated sample size was 47 patients; maintenance was deemed efficacious if at least 19 patients were progression-free survivors at 1 year. All enrolled patients were included in primary analyses, with the exception of patients who post-hoc objectively did not meet the eligibility criteria (modified intention-to-treat). This study is registered withclinicaltrials.gov registry, numberNCT00799513 . Findings: Between March 24, 2009, and Dec 22, 2015, we recruited 48 patients. 46 of 48 enrolled patients were assessable (two patients had unconfirmed diagnoses). 36 (78%) of 46 patients had de novo DLBCL and ten (22%) of 46 patients had transformed DLBCL. At a median follow-up of 25 months (IQR 12–56), 556 lenalidomide courses had been delivered, with an average mean of 12 courses (range 3–41) per patient; 19 patients were still in treatment at a median follow-up of 25 months. Lenalidomide was well tolerated; with the exception of neutropenia, grade 3–4 toxicities were uncommon. We recorded ten severe adverse events in nine patients due to febrile neutropenia (n=4), diarrhoea (n=2), melena, stroke, vomiting, and intestinal infarction; all but one patient recovered, and six of these patients continued with lenalidomide treatment. The exception was the only death due to toxicity (intestinal infarction). At 1 year from trial registration, 28 patients were progression free, which was much higher than the predetermined efficacy threshold. During the whole observation period, 21 events occurred: progressive lymphoma in 19 patients, death due to toxicity in one, death while off therapy in one, 1-year progression-free survival was 70% (95% CI 57–83). Interpretation: With the limitations of a non-randomised design, this trial supports the use of lenalidomide maintenance in patients with chemo-sensitive relapse of DLBCL who are not eligible for ASCT or who had relapse after ASCT. These results warrant further investigation of immunomodulatory drugs as maintenance in high-risk patients with DLBCL. Funding: Celgene Corp.